Development of phage resistance in clinical Escherichia coli and Klebsiella pneumoniae isolates - Vacker, Sanna (2024)
Antimicrobial resistance (AMR) is an escalating global health threat, attributable to the diminishing availability of efficient antibiotics against bacterial infections. Phage therapy is considered an alternative therapeutic solution to treat resistant infections. In phage therapy, the bacteria are treated with phages, which are natural viruses that infect bacteria. However, the development of phage resistance in bacterial communities can be affected by various host-associated factors. Mucin is a glycoprotein found in the mucosal layer of the human gut, which primarily protects the cellular surface. The interactions between bacteria and phages often occur in the mucous membrane. Also, recent studies have found the potential of mucin to alter phage-bacteria interactions. In this research, the evolution of phage resistance in Escherichia coli and Klebsiella pneumoniae strains was studied in the presence of mucin and antibiotics. First, bacterial growth was measured under various mucin and antibiotic concentrations in the absence of phage to select optimal conditions for the evolution experiment. In the evolution experiment, ESBL-producing E. coli and K. pneumoniae strains were sequentially exposed to phages, one at a time, in the presence of tetracycline and/or mucin. After the experiment, the development of phage resistance was tested in the exposed bacteria by a co-culture experiment. The results demonstrate that the phage-treated bacteria exhibited consistent development of phage resistance compared to the original strains. In an effort to develop efficient phage therapy, the findings of this research help comprehend the potential factors that may hamper the successful treatment of bacterial infections.